Wana Warrior Game as Animal Rescue Campaign Media - Adit Rama Putra; Erdhi Widyarto; Albertus Dwiyoga Widiantoro (Soegijapranata Catholic University, 2017)
Indonesia is a nation which rich of biodiversity. Various vegetation and good supporting climate make Indonesia a comfortable homeland for some specieses. Deforestation and illegal hunting threatened some speciecess. Seeing that situation, there are many ways to avoid that , one of them is using game as the media.Wana Warrior is a game used as education media of animal saving. The concept of this game is using game as the medium for conveying the information through design and gameplay which attract the players and they can learn without they realize from the provided information. Using Agenda Setting theory, provided informations are selected important issues. So players are focused only on provided issues. The result of the research shows “Wana Warrior” game can educate people about animal biodiversity, especially, in Indonesia.